INFORMATION TECHNOLOGY DIFFUSION OF FACULTY IN CEBU TECHNOLOGICAL UNIVERSITY NORTH DOMAIN - Himang, Celbert M.; Villaganas, Victor D.; Burgos, Rodulfo R.; Himang, Melanie M. (Journal of Agriculture and Technology Management, 2012)
The objective of this study was to determine status of the information technology diffusion in the CTU North Domain, that is, the characteristics of IT Early Adopters (EAs) and Mainstream Faculty (MF) in terms of level of computer experience, perceptions on the motivations and incentives of IT , the barriers of IT adoption and the preferred learning IT in terms of method, support and accessing information. There were evidences to support that early adopters were different from the mainstream faculty members of the CTU North Domain in the level of computer experience, personal and information technology adoption profiles. Early adopters and mainstream faculty members did not differ in their perception on the effect of information technology to teaching and learning and they do not vary considerably in their perception on what factors that motivate or prevent information technology adoption in teaching and learning. Moreover, the two groups do not differ significantly in their preferences on the methods of learning, getting support and accessing information technology innovation. Findings of this study support with Rogers’ theory of diffusion of innovation as applied in information technology adoption.